Geology of Kampung Batu Papan, Gua Musang and maturity assessment of petroleum crude oil from Field 1 - Mohd Hariz Shafee (2016)
Gua Musang, located in the south of Kelantan, is in Gua Musang Formation which age from Middle Permian to Upper Triassic. The purpose of this study is to execute a general geology of Kampung Batu Papan, Gua Musang and assess the maturity of petroleum crude oil from Field 1. The study area is located in Kampung Batu Papan, Gua Musang where geological features such as joints, beddings and faults were found. Desk study was conducted by revising some literatures related to the research topic and the study area. Fieldwork was planned to collect data, samples and photographs. Geological mapping was carried out to ﬁnd out the lithology and inspect all these features in accordance to their geological characteristics. There are three main rock types in this area; igneous, sedimentary and metamorphic rocks. The igneous rock consists of granite and rhyolite, sedimentary rock consists of shale, sandstone and limestone while metamorphic rock consists of phyllite. A geological map with cross section was produced by using ArcMap. For maturity assessment of petroleum crude oil from Field 1, one crude oil sample was assessed geochemically to determine its maturity and some relations with depositional environment conditions. Results reveal that it is mainly oxic depositional environment inferred from Pr/Ph ratios which is 2.88. On the basis of this study, the studied sample is thermally mature for hydrocarbon generation as indicated by biomarker thennal maturity parameters. From the waxiness index and terrigenous/aquatic ratio (TAR), it can be deduced that it is more terrigenous organic materials. Biomarker maturity parameters such as Tș/(Tș + Tṃ), C₃₀Mor/C₃₀H and 20S/(20S + 20R) C₂₉ sterane ratios also suggest that the sediments have reached the early to peak stages of hydrocarbon generation.